2003
DOI: 10.1023/a:1023409516739
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper reports on a study of individual variability in the relationship between negative mood and sexuality in men. Part 1 involves a questionnaire survey of 919 white heterosexual men, asking what typically happens to sexual interest and response when (a) depressed and (b) anxious/stressed, using the Mood and Sexuality Questionnaire (MSQ). Trait measures of sexual inhibition and excitation, depression, anxiety, and sensation seeking were also used. Relationships between trait measures and MSQ scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
80
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(100 citation statements)
references
References 23 publications
12
80
2
3
Order By: Relevance
“…There is one consistent finding that stands in contrast to the studies reviewed above: Three studies have found that some men and women experiencing depressive symptoms report elevated desire (Bancroft et al, 2003a; Frohlich & Meston, 2002; Nofzinger et al, 1993). Nofzinger et al (1993) found that this relationship was specific to episodes of atypical depression, and was not evident in anhedonic, endogenous, or melancholic depression.…”
Section: Part 2: Evidence That Supports the Formation Of The Hypothesmentioning
confidence: 89%
See 1 more Smart Citation
“…There is one consistent finding that stands in contrast to the studies reviewed above: Three studies have found that some men and women experiencing depressive symptoms report elevated desire (Bancroft et al, 2003a; Frohlich & Meston, 2002; Nofzinger et al, 1993). Nofzinger et al (1993) found that this relationship was specific to episodes of atypical depression, and was not evident in anhedonic, endogenous, or melancholic depression.…”
Section: Part 2: Evidence That Supports the Formation Of The Hypothesmentioning
confidence: 89%
“…Nofzinger et al (1993) found that this relationship was specific to episodes of atypical depression, and was not evident in anhedonic, endogenous, or melancholic depression. It seems likely that these studies may be describing the same phenomenon, as Frohlich and Meston (2002) and Bancroft et al (2003a) did not test for features of atypical depression, which can manifest as mild symptoms of major depression on self-report inventories (e.g., Fabre & Smith, 2012). A specific relationship between atypical depression and elevated desire would also be consistent with the finding that atypical depression is associated with lower rates of sexual dysfunction than major depression in men and women (Fabre, Clayton, Smith, Goldstein & Derogatis, 2013; Fabre & Smith, 2012), and could be explained by the mood reactivity to potential positive events in atypical depression, which may reinforce sexual approach behaviors.…”
Section: Part 2: Evidence That Supports the Formation Of The Hypothesmentioning
confidence: 99%
“…First, Odlaug et al (2013) found a lifetime history of Social Anxiety Disorder to be more prevalent among students who reported "out of control" sexual fantasies/behavior (versus those who did not). Second, whereas negative affective states may diminish sexual interest among less compulsive individuals, sometimes such states appear to enhance sexual interest among more compulsive individuals (e.g., Bancroft et al, 2003;Grov, Golub, Mustanski, & Parsons, 2010). Third, nearly half of Bancroft and Vukadinovic's (2004) self-identified sample of sex addicts used language suggestive of dissociative processes when describing episodes of "acting out" sexually.…”
Section: Sexual Compulsivitymentioning
confidence: 99%
“…Moreover, at clinically significant levels, social anxiety has been linked-among other things-to arousal difficulties and loss of desire during sexual episodes (Bodinger et al,188 C. T. Burris and K. M. Schrage 2002). On the other hand, stress/anxiety that is not attributed to social evaluative cues can sometimes facilitate not only increased sexual interest but also situation-specific sexual arousal in men and women (e.g., Bancroft et al, 2003;Bradford & Meston, 2006;Dèttore, Pucciarelli, & Santarnecchi, 2013;Goldey & van Anders, 2012;Lykins, Janssen, & Graham, 2006;Seto, 1992).…”
mentioning
confidence: 99%
“…Disgust sensitivity is a kind of special emotion related to sexual risk behaviors (Bancroft et al, 2003). Fessler and Navarrete (2003) noted that disgust sensitivity has the potential to “reduce participation in biologically suboptimal sexual behaviors” (p. 406).…”
Section: Introductionmentioning
confidence: 99%